2017
DOI: 10.17306/j.afs.0505
|View full text |Cite
|
Sign up to set email alerts
|

Effect of jasmonic acid and yeast extract elicitation on low-molecular antioxidants and antioxidant activity of marjoram (Origanum majorana L.)

Abstract: Marjoram (Origanum majorana L.), commonly known as sweet marjoram, is a plant from the Lamiaceae family, which is cultivated mainly for its aromatic leaves used for culinary purposes (Prerna and Vasudeva, 2015). This herb has been traditionally used, especially in India, for thousands of years for the treatment of gastrointestinal disturbances, cough, and bronchial diseases (Saxena et al., 2016 ABSTRACTBackground. Elicitation, which is a way of inducing plant secondary metabolism, may be an effective method f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…A majority of research on the use of yeast extract as a biotic elicitor reported in the literature was conducted in suspension cell cultures, and only a few reports present the effect of YE application to plants in vivo. In the research conducted by Złotek [16], elicitation with YE, as in the present study, did not increase the content of phenolic compounds but significantly increased the content of ascorbic acid and chlorophyll in marjoram leaves. Additionally, another biotic elicitor, chitosan oligosaccharide, was an effective stimulator of polyphenol production by oregano plants [25].…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…A majority of research on the use of yeast extract as a biotic elicitor reported in the literature was conducted in suspension cell cultures, and only a few reports present the effect of YE application to plants in vivo. In the research conducted by Złotek [16], elicitation with YE, as in the present study, did not increase the content of phenolic compounds but significantly increased the content of ascorbic acid and chlorophyll in marjoram leaves. Additionally, another biotic elicitor, chitosan oligosaccharide, was an effective stimulator of polyphenol production by oregano plants [25].…”
Section: Discussionsupporting
confidence: 67%
“…As indicated in our study, the antiradical and reducing potential of lovage extracts was evaluated mostly by JA elicitation (especially JA2), while the ability to chelate iron ions increased the most after the YE2 elicitation (Figure 1). Similarly, in studies on marjoram and basil elicitation, the use of jasmonic acid resulted in an increase in antiradical properties (marjoram and basil) and reducing power (marjoram) of this herb [16,21], as well as improvement of DPPH-free radical scavenging activity of the sweet basil after 0.1 and 0.5 mM methyl jasmonate treatments [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on the elicitation of herbs are also being conducted. Złotek et al [51] studied the effect of elicitors on Origanum majorana L. According to their results, jasmonic acid elicitation significantly increased the carotenoid content and yeast extract increased the antioxidant content. Foliar application of methyl jasmonate and salicylic acid increased (2-fold) the concentration of folic acid in coriander foliage, and folates demonstrated higher stability during processing and storage [52].…”
Section: Elicitationmentioning
confidence: 99%
“…Modified growth and development, can have benifical effects on morphological, physiological, biochemical characteristics than increased biomass yield production and quality [63] [64], Effortful studies has been undertaken for motivtation. innate ability of elicitation in producing extent of bioactive SMs and/or biomass production [65] Alos elicitation has been applied to stimulate the medicinal plants production through organic and agrochemical management contributing [66], Elicitation have related yet distinct role in regulation of plant and pathogen attack, that cause hug loss in yield production under agrochemical traditional agriculture [67], Biotic and abiotic stress/eliators, induces, the production of oxygen derived radicals such as H 2 O 2 (hydrogen peroxide), superoxide molecules, hydroxyl (OH) and/or oxygen radicals (O) that are the first line of defense for stressed plant [68] which are often implicated to induce systemic resistance (ISR) by regulating the expression genes involved for production and accumulation of SMs, phytoalexins (PAs) which non specific toxins characterized brood spectrum bio-anti-pesticides and bio-anti-micro biocides making them improving against microbial diseases and pests infestation [64] [69] [70] [71].…”
Section: Introductionmentioning
confidence: 99%